Correlation between academic hardiness and subjective well-being among teenagers: the chain mediating role of academic passion and academic self-efficacy - Zhou, Lihua; Tang, Mingdan; Du, Xuejuan; Chen, Jian (Frontiers in Psychology, 2025)
Enhancing the positive qualities of adolescents and their capacity to actively attain well-being is a crucial objective in education. The correlation among academic hardiness, academic passion, academic self-efficacy and subjective well-being was explored by an investigation which was conducted among 805 junior high school students (ages 12–15) using the Academic Hardiness Scale, Academic Passion Scale, Academic Self-efficacy Scale and Subjective Well-being Index Scale in this study. The findings indicated that academic hardiness is the variable most closely related to subjective well-being; academic self-efficacy plays a significant mediating role between academic hardiness and subjective well-being; academic hardiness is positively associated with subjective well-being through the chain mediation pathway from academic harmonious passion or obsessive passion to academic self-efficacy. These results suggest that cultivating academic hardiness in teenagers is positively significant for improving their positive academic emotional experience, academic self-efficacy and overall subjective well-being.